Association between fluid balance, muscle strength, and muscle quality in critically ill patients: a retrospective observational study - Nicolas Arancibia-Ramirez; Yorschua Jalil Contreras; Alexis Silva; L. Felipe Damiani; Jorge Molina; Cheryl E. Hickmann (Intensive Care Medicine Experimental, 2026)
Abstract Background Intensive Care Unit–acquired weakness (ICUAW) is a frequent complication that significantly impairs functional recovery in critically ill patients. Fluid overload during critical illness has been associated with adverse outcomes, but its relationship with peripheral muscle quality and strength remains uncertain. This study aimed to evaluate the association between cumulative fluid balance, ultrasound-assessed muscle quality, and muscle strength in critically ill patients. Patients and methods We conducted a retrospective analysis of routinely collected data between May and October 2024 in adult ICU patients who were deeply sedated, mechanically ventilated, and had an ICU length of stay ≥24 hours. Muscle and subcutaneous tissue measurements were obtained using ultrasound of the vastus intermedius and rectus femoris within the first 24 hours of ICU admission (day 1) and at clinical awakening. Muscle quality was assessed at both time points using the Heckmatt scale. Global muscle strength was assessed only at clinical awakening using the Medical Research Council Sum Score (MRC-SS), once patients were able to follow commands. Patients without complete ultrasound measurements at both time points were excluded from the final analysis. Results Eighty patients were included (mean age 51 ± 14 years; APACHE II score 18 ± 5). The main admission diagnoses were predominantly respiratory and septic conditions. Mean cumulative fluid balance at awakening was 2400 ± 800 mL. From ICU admission to awakening, quadriceps thickness decreased, whereas subcutaneous tissue thickness increased and muscle quality deteriorated, as reflected by higher Heckmatt scores. At awakening, cumulative fluid balance showed a strong inverse correlation with global muscle strength (rho = −0.70, p < 0.001) and a moderate positive correlation with subcutaneous tissue thickness. Muscle quality assessed by the Heckmatt scale was moderately inversely correlated with MRC-SS (rho = −0.43, p< 0.001). In multivariable analysis adjusted for age, disease severity, and duration of mechanical ventilation, cumulative fluid balance remained independently associated with lower muscle strength at awakening. Conclusions Qualitative muscle ultrasound assessment using the Heckmatt scale provides complementary information to muscle thickness measurements. The observed association between cumulative fluid balance and poorer muscle quality suggests that fluid status should be considered when interpreting qualitative muscle ultrasound findings in critically ill patients.